Tyre contact length on dry and wet road surfaces measured by three-axial accelerometer. (February 2015) - Matilainen, Mika; Tuononen, Ari
Abstract: We determined the tyre contact length on dry and wet roads by measuring the accelerations of the inner liner with a three-axial accelerometer. The influence of the tyre pressure, driving velocity, and tread depth on the contact length was studied in both types of road surface conditions. On dry asphalt the contact length was almost constant, regardless of the driving velocity. On wet asphalt the presence of water could be detected even at low driving velocities (e.g. 20 km/h for a worn tyre) as the contact length began to decrease from that found in the dry asphalt situation. In addition to improving the performance of active safety systems and driver warning systems, the contact length information could be beneficial for classifying and studying the aquaplaning behaviour of tyres. Highlights: Tyre–road contact length was determined by measuring the 3D-accelerations of the tyre carcass. Experiments were performed on dry and wet road surfaces with wide span of parameters. The decrease of contact length on wet roads can be detected already at low driving velocities. The system can detect the vanishing contact length during full aquaplaning. Real-time tyre–road contact length information could benefit both the drivers and active safety systems.